Higher Education: Handbook of Theory and Research. Volume 28 - Paulsen, Michael B., Ed (Higher Education: Handbook of Theory and Research : Volume 28, 2013)
Published annually since 1985, the "Handbook" series provides a compendium of thorough and integrative literature reviews on a diverse array of topics of interest to the higher education scholarly and policy communities. Each chapter provides a comprehensive review of research findings on a selected topic, critiques the research literature in terms of its conceptual and methodological rigor, and sets forth an agenda for future research intended to advance knowledge on the chosen topic. The "Handbook" focuses on a comprehensive set of central areas of study in higher education that encompasses the salient dimensions of scholarly and policy inquiries undertaken in the international higher education community. Each annual volume contains chapters on such diverse topics as research on college students and faculty, organization and administration, curriculum and instruction, policy, diversity issues, economics and finance, history and philosophy, community colleges, advances in research methodology, and more. The series is fortunate to have attracted annual contributions from distinguished scholars throughout the world. This book contains the following chapters: (1) You Don't Have to Be the Smartest Person in the Room (George D. Kuh); (2) Student Engagement: Bridging Research and Practice to Improve the Quality of Undergraduate Education (Alexander C. McCormick, Jillian Kinzie, and Robert M. Gonyea); (3) From When and Where I Enter: Theoretical and Empirical Considerations of Minority Students' Transition to College (Deborah Faye Carter, Angela Mosi Locks, and Rachelle Winkle-Wagner); (4) Social Networks Research in Higher Education (Susan Biancani and Daniel A. McFarland); (5) Research Integrity and Misconduct in the Academic Profession (Melissa S. Anderson, Marta A. Shaw, Nicholas H. Steneck, Erin Konkle, and Takehito Kamata); (6) Instrumental Variables: Conceptual Issues and an Application Considering High School Course Taking (Rob M. Bielby, Emily House, Allyson Flaster, and Stephen L. DesJardins); (7) On the Meaning of Markets in Higher Education (William E. Becker and Robert K. Toutkoushian); (8) Learning Strategies, Study Skills, and Self-Regulated Learning in Postsecondary Education (Philip H. Winne); (9) The History and Historiography of Teacher Preparation in the United States: A Synthesis, Analysis, and Potential Contributions to Higher Education History (Christine A. Ogren); (10) A Review and Critique of the Literature on Community College Students' Transition Processes and Outcomes in Four-Year Institutions (Peter Riley Bahr, Christie Toth, Kathryn Thirolf, and Johanna C. Massé); (11) Public Policy and Higher Education Attainment in a Twenty-First-Century Racial Demography: Examining Research from Early Childhood to the Labor Market (Stella M. Flores and Leticia Oseguera); (12) Advancing the Study of Student-Faculty Interaction: A Focus on Diverse Students and Faculty (Darnell Cole and Kimberly A. Griffin); and (13) State Support of Higher Education: Data, Measures, Findings, and Directions for Future Research (David A. Tandberg and Casey Griffith).